TEACHING SIGHT WORDS AND COMMON PHRASES TO IMPROVE EARLY READING FLUENCY (Лучшие интеллектуальные исследования, 2025)
Abstract:This paper explores the role of teaching sight words and common phrases in developing early reading fluency among young learners. Sight words are frequently used words that children are encouraged to recognize instantly, without needing to decode them phonetically. By mastering these words and familiar phrases, students can read more smoothly and with greater confidence. The study highlights effective strategies for teaching sight words, such as repetition, visual aids, and contextual reading. It also emphasizes the importance of building a strong foundation in word recognition to support reading comprehension and long-term literacy development.